Development of stiff, strong, yet tough composites by the addition of solvent exfoliated graphene to polyurethane - COLEMAN, JONATHAN; KHAN, UMAR; O'NEILL, ARLENE; MAY, PETER (My University, 2010)
We have prepared graphene dispersions, stabilised by polyurethane in tetrahydrofuran and dimethylformamide. These dispersions can be drop-cast to produce free-standing composite films. The graphene mass fraction is determined by the concentration of dispersed graphene and can be controllably varied from 0% to 90%. Raman spectroscopy and Helium ion microscopy show the graphene to well-dispersed and well-exfoliated in the composites, even at mass fractions of 55%. On addition of graphene, the Young?s modulus and stress at 3% strain increase by ?100, saturating at 1 GPa and 25 MPa respectively for mass fractions above 50wt%. While the ultimate tensile strength does not vary significantly with graphene content, the strain at break and toughness degrade heavily on graphene addition. Both these properties fall by ?1000 as the graphene content is increased to 90wt%. However, the rate of increase of Young?s modulus and stress at 3% strain with mass fraction is greater than the rate of decrease of ductility and toughness. This makes it possible to prepare composites with high modulus, stress at low strain and ultimate tensile strength as well as relatively high toughness and ductility. This could lead to new materials that are stiff, strong and tough.
PUBLISHED
Keywords: Condensed matter physics; graphene dispersions; Nanoscience & Materials